PENGEMBANGAN MEDIA CULTURE SMART BOX BERBASIS GAMIFIKASI TABUDI UNTUK MENINGKATKAN KEMAMPUAN KOLABORASI SISWA - Nuril Afidah; Cindya Alfi; Ragil Tri Oktaviani (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
Science and social science learning on Indonesian cultural material in elementary schools is often faced with a lack of concrete learning media, resulting in low student participation and collaboration skills. This study aims to develop and test the validity, feasibility, and effectiveness of Culture Smart Box media based on TABUDI gamification in improving the collaboration skills of fourth-grade students at SDI Ma’arif Tawangsari Garum, Blitar Regency. This research and development study applies the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. Data were collected using observation, interviews, and student collaboration questionnaires, which were analyzed qualitative-descriptively and quantitatively using the N-Gain test. The validation results by material experts reached 90% categorized as "Very Valid," while media experts showed 96% categorized as "Very Valid." The media feasibility test based on teacher response achieved a score of 100% categorized as "Very Feasible." The implementation of Culture Smart Box media based on TABUDI gamification contributes to improving collaboration skills with an average N-Gain score of 0.76, which falls into the "High" category. ABSTRAK Pembelajaran IPAS materi kebudayaan Indonesia di sekolah dasar sering kali dihadapkan pada keterbatasan bahan ajar konkret yang berdampak pada rendahnya partisipasi serta kemampuan kolaborasi siswa. Penelitian ini bertujuan untuk mengembangkan serta menguji validitas, kelayakan, dan efektivitas media Culture Smart Box berbasis gamifikasi TABUDI dalam meningkatkan kemampuan kolaborasi siswa kelas IV SDI Ma’arif Tawangsari Garum Kabupaten Blitar. Penelitian pengembangan ini menerapkan model ADDIE yang meliputi tahap analisis, perancangan, pengembangan, implementasi, dan evaluasi. Data dikumpulkan melalui instrumen observasi, wawancara, serta angket kemampuan kolaborasi siswa yang dianalisis secara deskriptif kualitatif dan kuantitatif menggunakan uji N-Gain. Hasil validasi oleh ahli materi memperoleh persentase sebesar 90% dengan kategori "Sangat Valid", sedangkan validasi oleh ahli media mencapai 96% dengan kategori "Sangat Valid". Uji kelayakan media berdasarkan respons guru memperoleh persentase 100% dengan kategori "Sangat Layak". Penerapan media Culture Smart Box berbasis gamifikasi TABUDI berkontribusi dalam meningkatkan kemampuan kolaborasi siswa dengan perolehan rerata skor N-Gain sebesar 0,76 yang tergolong dalam kategori "Tinggi".